Prevalence of Catatonia and Its Moderators in Clinical Samples: Results from a Meta-analysis and Meta-regression Analysis. (13th November 2017) - Solmi, Marco; Pigato, G Giorgio; Roiter, Beatrice; Guaglianone, Argentina; Martini, Luca; Fornaro, Michele; Monaco, Francesco; Carvalho, Andrè F; Stubbs, Brendon; Veronese, Nicola; Correll, Christoph U
Abstract: Catatonia is an independent syndrome that co-occurs with several mental and medical conditions. We performed a systematic literature review in PubMed/Scopus until February 2017 and meta-analyzed studies reporting catatonia prevalence. Across 74 studies (cross-sectional = 32, longitudinal = 26, retrospective = 16) providing data collected from 1935 to 2017 across all continents, mean catatonia prevalence was 9.0% ( k = 80, n = 110764; 95% CI = 6.9–11.7, I 2 = 98%, publication bias P < .01), decreasing to 7.8% ( k = 19, n = 7612, 95% CI = 7–8.7, I 2 = 38.9%) in a subgroup with low heterogeneity. Catatonia prevalence was 23.9% ( k = 8, n = 1168, 95% CI = 10–46.9, I 2 = 96%) in patients undergoing ECT/having elevated creatinine phosphokinase. Excluding ECT samples, the catatonia prevalence was 8.1% ( k = 72, n = 109606, 95% CI = 6.1–10.5, I 2 = 98%, publication bias P < .01), with sensitivity analyses demonstrating that country of study origin ( P < .001), treatment setting ( P = .003), main underlying condition ( P < .001), and sample size ( P < .001)moderated catatonia prevalence, being highest in Uganda (48.5%, k = 1) and lowest in Mexico (1.9%, 95% CI = 0.4–8.8, I 2 = 67%, k = 2), highest in nonpsychiatric out- or inpatient services (15.8%, 95% CI = 8.1–28.4, I 2 = 97%, k = 15)and lowest in psychiatric outpatients services (3.2%, 95% CI = 1.7–6.1, I 2 = 50%, k = 3), highest in presence of medical or neurological illness with no comorbid psychiatric condition (20.6%, 95% CI = 11.5–34.2, I 2 = 95%, k = 10)and lowest in mixed psychiatric samples (5.7%, 95% CI = 4.2–7.7, I 2 =98%, k = 43), highest in studies with sample sizes <100 (20.7%, 95% CI = 12.8–31.6, I 2 = 90%, k = 17) and lowest in studies with sample sizes >1000 (2.3%, 95% CI = 1.3–3.9, I 2 = 99%, k = 16). Meta-regression showed that smaller sample size ( P < .01) and less major depressive disorder ( P = .02) moderated higher catatonia prevalence. Year of data collection did not significantly moderate the results. Results from this first meta-analysis of catatonia frequencies across time and disorders suggest that catatonia is an epidemiologically and clinically relevant condition that occurs throughout several mental and medical conditions, whose prevalence has not decreased over time and does not seem to depend on different rating scales/criteria. However, results were highly heterogeneous, calling for a cautious interpretation.